Functionalized role of highly porous activated carbon in bismuth vanadate nanomaterials for boosted photocatalytic hydrogen evolution and synchronous activity in water. (18th November 2021) - Tahir, Muhammad Bilal; Nawaz, Tasmia; Sagir, Muhammad; Alzaid, Meshal; Alrobei, Hussein; Shahzad, Khurram; Ali, Arshid Mahmood; Muhammad, Shabbir
Abstract: Energy crises and water pollution have become the key challenges in current era of technology. In this research work, activated carbon modified BiVO4 photocatalysts have been prepared using simple hydrothermal methods for efficient hydrogen evolution through water splitting under visible light irradiation and degradation, simultaneously. The properties of the synthesized photocatalysts were studied through SEM, UV, XRD, BET and PL emission spectroscopy. The 4%AC/BiVO4 exhibited highest degradation efficiency ≈98% in 60 min and production of hydrogen energy ≈510 h −1 g −1 which is much higher when compared to pure BiVO4 . The enhancement in the efficiency was due to large surface area, large absorption region. High crystallinity, small band gap and synergetic effect between the composites. The activated carbon based BiVO4 composites showed high stability which shows its vital role in practical applications. Highlights: Activated carbon/BiVO4 composite photocatalysts were obtained via the facile hydrothermal method. Development of Ac/BiVO4 system to improve the separation of charge-carriers. Efficient separation and easy flow of charge-carriers for hydrogen evolution and degradation.